Migration processes and socio-economic development: interactions and regulatory policy - Lupak, R.; Mizyuk, B.; Zaychenko, V.; Kunytska-Iliash, M.; Vasyltsiv, T.; Зайченко, В. В. (Ін-т східноєвропейських досліджень та консалтингу, 2022)
Purpose. The purpose of the article is to test the developed methodical approach to analyzing the relationship and impact of the population migration and socio-economic development of the state, as well as to identify migration factors that affect key parameters of the national economy and vice versa – social and economic indicators that determine the intensity of migration, the substantiation of conclusions on this basis for the state policy of the regulation of migration processes for the preservation and development of the human resources of Ukraine. Methodology / approach. The research methodology involves ten successive stages: (1) selection of indicators that characterize the socio-economic development of the state by 5 subindices: socio-demographic stability; social development; labor market and employment; quality of life of the population; sustainable economic development; (2) formation of a database under the values of indicators by the regions of Ukraine for the period 2010–2020; (3) division of indicators into stimulators and disincentives and their rationing; (4) formation of homogeneous time series; (5) determination of the dynamic weighing coefficients of indicators and their groups (sub-indices); (6) calculation of weighted coefficients of indicators; (7) construction of weighted coefficients of the sub-indices of socio-economic development; (8) calculation of the integral coefficient of the socioeconomic development of Ukraine; (9) calculation of migration indicators (border crossing balance by Ukrainians and foreigners) of the population by regions and in Ukraine as a whole; (10) construction of time series of the integral indices of migration and socio-economic development by years and regions, assessment of the strength and direction of the relationships between migration indicators and the indicators of socio-economic development, as well as between the indicators of migration and arrival from other regions; from abroad (including per 10 thousand population), in urban settlements, in rural areas of Ukraine in 2010–2020. Results. The development and testing of a methodical approach to assessing the impact of migration processes on the socio-economic development of Ukraine and its regions allowed identifying the strength of the relationships between migration, social, and economic indicators, the impact of these processes on the human resources in Ukraine. The greatest interdependence between the socio-economic environment and stationary emigration is found in terms of the disposable income of the population, average monthly nominal wages, the unemployment rate, average state social assistance, housing and crime rates. Concerning immigration, close relationships are found with the economic indicators of regional development, small business performance, the unemployment rate, average monthly nominal wages, informal employment, the volumes of budget funding for social protection goals, and the disposable income of the population. One of the dominant factors of immigration is education, which confirms the untapped potential of attracting foreigners for employment. Originality / scientific novelty. The novelty of the research results is in the development of methodical approaches to analyzing the interaction of migration and socio-economic processes with the formation of an algorithm of integral assessment by the components of socio-demographic stability, social development, employment, quality of life, sustainable economic development. The author’s methodical approach to assessment is offered, which allows carrying out empirical modeling and the assessment of the impact of socio-economic development on the intensity of migration processes, substantiating priority areas of the state regulation of migration potential (including wages, personal and state security). Practical value / implications. The practical significance of the research results is in the considerable improvement of the information and analytical basis for the formation of an effective state policy for the regulation of migration processes in Ukraine. Using migration, the bodies of the State Migration Service of Ukraine and the State Statistics Service of Ukraine can analyze the impact (including potential, forecast) of different types (external / internal, stationary / labor, urban / rural settlements, etc.) of migration on the social-economic development of the state and its territories, as well as model the direction and intensity of migration, its structure depending on changes in the values of certain parameters of the socio-economic development of the country and its regions. Мета. Мета дослідження – апробація розробленого методичного підходу до аналізування зв’язку та впливу міграції населення й соціально-економічного розвитку держави, а також ідентифікація міграційних чинників, які позначаються на ключових параметрах функціонування національної економіки та навпаки – соціальних та економічних індикаторів, які визначають інтенсивність міграції, обґрунтування на цій основі висновків для державної політики регулювання міграційних процесів задля збереження й розвитку людських ресурсів України. Методологія / методика / підхід. Методологія дослідження передбачає проходження десяти послідовних етапів: (1) підбір індикаторів, які характеризують соціально-економічний розвиток держави за 5 субіндексами: соціально-демографічна стабільність; соціальний розвиток; ринок праці та сфера зайнятості; якість життя населення; стійкий економічний розвиток; (2) формування бази даних за значеннями індикаторів за регіонами України за часовий період 2010–2020 рр.; (3) розподіл індикаторів на стимулятори й дестимулятори та їх нормування; (4) формування однорідних динамічних рядів даних; (5) визначення динамічних вагових коефіцієнтів індикаторів та їх груп (субіндексів); (6) розрахунок зважених коефіцієнтів індикаторів; (7) побудова зважених коефіцієнтів субіндексів соціально-економічного розвитку; (8) розрахунок інтегрального коефіцієнта соціально-економічного розвитку України; (9) розрахунок показників міграції населення (сальдо перетину кордону українцями та іноземцями) за регіонами та в Україні загалом; (10) побудова динамічних рядів інтегральних індексів міграції та соціально-економічного розвитку за роками та за регіонами, оцінювання сили та напряму зв’язків між індикаторами міграції та показниками соціально-економічного розвитку, а також між індикаторами міграції та прибуття населення з інших областей; із-за кордону (у т. ч. на 10 тис. населення), у міські поселення, у сільську місцевість в Україні за 2010–2020 рр. Результати. Розробка та апробація методичного підходу до оцінювання впливу міграційних процесів на соціально-економічний розвиток України та її регіонів дозволили ідентифікувати силу зв’язків між міграційними, соціальними й економічними індикаторами, вплив зазначених процесів на людські ресурси в Україні. Найбільша взаємозалежність між соціально-економічним середовищем і стаціонарною еміграцією виявлена за показниками наявного доходу населення, середньомісячною номінальною заробітною платою, рівнем безробіття, середнім розміром державної соціальної допомоги, забезпеченістю населення житлом і рівнем злочинності. Що стосується імміграції, то тісні взаємозв’язки виявлені з економічними показниками регіонального розвитку, результатами діяльності малих підприємств, рівнем безробіття, середньомісячною номінальною заробітною платою, неформальною зайнятістю, обсягами бюджетного фінансування соціально-захисних цілей, наявним доходом населення. Одним із домінуючих чинників імміграції є освітній, що підтверджує невикористаний потенціал залучення іноземців з метою працевлаштування. Оригінальність / наукова новизна. Новизна результатів дослідження полягає в розвитку методичних підходів до аналізування взаємовпливу міграційних і соціально-економічних процесів із формуванням алгоритму інтегрального оцінювання за складниками соціально-демографічної стабільності, соціального розвитку, зайнятості, якості життя, стійкого економічного розвитку. Запропоновано авторський методичний підхід до оцінювання, що дозволяє здійснювати емпіричне моделювання та оцінку впливу соціально-економічного розвитку на інтенсивність міграційних процесів, обґрунтовувати пріоритетні сфери державного регулювання потенціалу міграції (зокрема щодо оплати праці, захищеності особи та безпеки держави). Практична цінність / значущість. Практична значущість результатів дослідження полягає в значному покращенні інформаційно-аналітичного базису формування ефективної державної політики регулювання міграційних процесів в Україні. Із використанням міграції органи Державної міграційної служби України та Державної служби статистики України можуть аналізувати вплив (у т. ч. потенційний, прогнозний) різних видів (зовнішня / внутрішня, стаціонарна / трудова, міські / сільські поселення й т. ін.) міграції на соціально-економічний розвиток держави та її територій, а також моделювати напрям й інтенсивність міграції, її структуру залежно від зміни значень параметрів соціально-економічного розвитку країни та її регіонів.
Міграційні процеси та соціально-економічний розвиток: взаємовпливи та політика регулювання
Keywords: human resources; population migration; socio-economic development; regions; rural and urban areas; regulatory policy; людські ресурси; міграція населення; соціально-економічний розвиток; регіони; сільські та міські територій; політика регулювання